HUBUNGAN PENGETAHUAN IBU TENTANG STATUS GIZI DENGAN PERAWATAN BALITA KURUS (WASTING) DI PUSKESMAS OEPOI KOTA KUPANG - yustika tresiani pehe; Istha Leani Muskananfola; Maria Yasintha Goa (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
Introduction: Wasting is an acute nutritional problem, as a result of events that occur in a short time such as lack of food intake. Nutritional status is the state of the body as a result of consuming food and using nutrients. Efforts to achieve a good nutritional status of children under five cannot be separated from the knowledge of the mother as a caregiver because the mother is the one who is responsible for providing food regarding nutritional status in the care of toddlers. Objective: to determine the relationship between mother's knowledge about nutritional status and treatment for wasting toddlers at the Oepoi Health Center, Kupang City. Methods: This research is a quantitative research with a cross sectional approach. The sample used is 127 mothers who have wasting toddlers. The sampling technique used is total sampling. Collecting data using a questionnaire on maternal knowledge and care for underweight toddlers (wasting). Results: This study found that most respondents had a sufficient level of knowledge as many as 64 people (50.4%), and poor care of wasting toddlers as many as 73 people (57.5%). The results of the Spearman Rho test prove that there is a significant relationship between the mother's knowledge of nutritional status and the treatment of wasting under-fives with p value = 0.003. Conclusion: This research is expected to have knowledge possessed by mothers regarding nutritional status about caring for toddlers in compiling food menus, choosing food ingredients, processing, serving and how to provide good and correct food so that the nutritional needs of toddlers can be met. Keywords: Mother's knowledge, nutritional status, care for wasting toddlers.